STRATEGI TANGGUNG JAWAB SOSIAL PERUSAHAAN GARMEN DALAM MENCIPTAKAN PRODUK RAMAH LINGKUNGAN DI INDONESIA - Ulfiyah, Siti Pujiati; Syafrinadina (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2024)
The garment industry has a significant environmental impact, making corporate social responsibility (CSR) increasingly important. This study examines the strategies used by garment companies in Indonesia to create eco-friendly products through CSR, as well as the human resource management (HRM) strategies that support these CSR initiatives. A qualitative method with a descriptive-analytical approach was used, with data collected through a literature study. The results show that garment companies are implementing various CSR strategies, such as using environmentally-friendly materials, efficient waste management, and involvement in environmental restoration programs. The three main HRM strategies are the development of employee capabilities, employee empowerment in waste management, and employee involvement in environmental restoration programs. However, there are still challenges related to regulatory compliance, implementation costs, and consumer awareness. Collaboration between the government, industry, and the community is necessary to create a more sustainable environment.